Enjoyment begets enjoyment: an experience sampling study on the impact of L2 teacher enjoyment on EFL learners’ learning enjoyment and willingness to communicate - Solhi, Mehdi; Elahi Shirvan, Majid; Benlioğlu, Belkıs (My University, 2024)
While previous studies have separately explored learner and teacher emotions in the context of second or foreign language (L2) learning, their dynamic associations over time remain underexplored. Additionally, the impact of these reciprocal interplays on learners' communication intention has not been taken into scrutiny in L2 research. The present study investigated the relationships between trajectories of foreign language teaching enjoyment (FLTE), foreign language learning enjoyment (FLE), and L2 willingness to communicate (WTC). Using an experience sampling method, data were collected from 9 English instructors and 162 students over two weeks. The dynamic structural equation modeling analysis revealed significant positive changes in actual and perceived FLTE, FLE, and L2 WTC. Specifically, a reciprocal relationship was found between teacher and student enjoyment, with L2 students' high FLE levels correlating with higher L2 WTC. Although student-perceived FLTE remained stable, L2 teachers’ actual enjoyment fluctuated, being influenced by FLE and L2 WTC. Additionally, L2 WTC significantly impacted teacher enjoyment. On average, teachers with more development in FLTE had students with more development in their FLE and L2 WTC. Overall, the findings underscore the dynamic interplay between teacher and student emotions in L2 learning context and its consequent positive impact on learners' communication intentions. In closing, the findings are discussed in connection with educational theories, and implications are drawn for L2 teaching.
Keywords: Experience Sampling Method; FLE; FLET; WTC